Persistent fever and hemoptoic sputum – clinical case - Mosca, Sara (2022)
Foreign body aspiration (FBA) is a common and serious problem in children. Considering that signs and symptoms can be non-specific and subtle, it is of utmost importance to recognize vulnerable patient groups, combine an accurate history with complete physical examination, and follow a structured diagnostic approach towards correct diagnosis. In the present case, a high index of suspicion was essential to prevent a delay in FBA diagnosis, discuss the appropriate management strategy and improve patient outcomes.